2010
DOI: 10.1080/02640410903518184
|View full text |Cite
|
Sign up to set email alerts
|

Offside decision making of assistant referees in the English Premier League: Impact of physical and perceptual-cognitive factors on match performance

Abstract: In the present study, we investigated the accuracy of offside judgements of assistant referees in the English Premier League. The moment in the match, the position and movement speed of the assistant referee, attacker and second-last defender, together with the angle of view for the assistant referee were all considered to underlie incorrect decisions. The error rate was 17.5% (868 of 4960 situations). As the English assistant referees tended not to signal in doubtful situations (c = 0.91), there was an overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 15 publications
4
68
3
6
Order By: Relevance
“…While Helsen et al (2006) and Catteeuw et al (2010b) reported frequencies of 0.5 and 4 non-flag decisions per match, respectively, Catteeuw et al, (2010a) and Oudejans et al (2005) elevated these situations to 24 and 49 per game, respectively. Following recent studies (Catteeuw et al, 2010a) we considered offside situations when the attacking player was 2 m or less from the offside line.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While Helsen et al (2006) and Catteeuw et al (2010b) reported frequencies of 0.5 and 4 non-flag decisions per match, respectively, Catteeuw et al, (2010a) and Oudejans et al (2005) elevated these situations to 24 and 49 per game, respectively. Following recent studies (Catteeuw et al, 2010a) we considered offside situations when the attacking player was 2 m or less from the offside line.…”
Section: Discussionmentioning
confidence: 99%
“…The main responsibility of officials is to guarantee the respect of the Laws of the Game and, in particular, Catteeuw, Helsen, Gilis, and Wagemans (2009a) showed role specificity for assessing foul play incidents by referees and for offside decision making by assistant referees. Therefore, an increasing interest has been placed in recent years on the decision making skills of officials during real match play (Catteeuw et al, 2010a(Catteeuw et al, , 2010bHelsen et al, 2006;Oudejans et al, 2005;van Quaquebeke & Giessner, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre las variables de análisis destacan la experiencia de arbitraje (Catteeuw, Helsen, Gilis, & Wagemans, 2009a;Catteeuw et al, 2009b;Catteeuw et al, 2009;Gilis et al, 2009), el rol posicional ocupado en el terreno de juego (Catteeuw et al, 2009a;Catteeuw et al, 2010;Catteeuw, Gilis, Wagemans, & Helsen, 2010a;Helsen et al, 2006), situación de medición , distancia (Button, 2006), ángulo de visionado (Catteeuw et al, 2010a) con que se percibe la acción de fuera de juego por parte del asistente o árbitro, posición del asistente justo en el momento del fuera de juego (Catteeuw et al, 2010;Helsen et al, 2006;Oudejans et al, 2005), e incluso momento temporal del partido en que se produce dicha acción de juego (Button, 2006;Helsen et al, 2006).…”
Section: Introductionunclassified